1993
DOI: 10.1039/jm9930300889
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, single-crystal structure and magnetic properties of orthorhombic CuNb2O6

Abstract: The conditions necessary for the synthesis of the two reported polymorphs of CuNb,O, from the binary oxides have been investigated. The black, orthorhombic phase has been prepared in a pure crystalline form and its single-crystal structure determined. It is isomorphous with the M"Nb,O, columbite system (orthorhombic, a = 14.019(11) A, b = 5.623(7) A, c = 5.107(7) A, space group Pbcn) but the CuO, octahedra display a large tetragonal distortion [Cu-0, 1.976(6) x 2, 1.973(6) x 2, and 2.383(6) x 2 A]. Above 225 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Pullar et al 22 reported a mixed phase CuNb 2 O 6 up to 1200°C, when it melted, and above 950°C a liquid phase lead to exaggerated or discontinuous grain growth (DGG). It has been suggested that once the monoclinic phase has been formed it is hard to obtain the single orthorhombic phase, although it can be obtained by annealing at 900°C, 34 stress induced by grinding the monoclinic phase, 35 or by heating to 1100°C (producing unsintered powder with a grain size of 15 μm) 36 …”
Section: Synthesis Of Columbite Ceramicsmentioning
confidence: 99%
“…Pullar et al 22 reported a mixed phase CuNb 2 O 6 up to 1200°C, when it melted, and above 950°C a liquid phase lead to exaggerated or discontinuous grain growth (DGG). It has been suggested that once the monoclinic phase has been formed it is hard to obtain the single orthorhombic phase, although it can be obtained by annealing at 900°C, 34 stress induced by grinding the monoclinic phase, 35 or by heating to 1100°C (producing unsintered powder with a grain size of 15 μm) 36 …”
Section: Synthesis Of Columbite Ceramicsmentioning
confidence: 99%
“…These layers are stacked along [001], and the copper ions set in a linear surrounding ensure the cohesion of the structure. The structure of CuNb 3 O 8 23 and CuNb 2 O 6 24 can be described in one step as they are both related to the same α-PbO 2 structure type ( Fig. 12).…”
Section: Influence Of the Copper Ions Mobility On The Displacement Phmentioning
confidence: 99%
“…These minerals are economically important since they are the major source of tantalum. In addition, they are very interesting from a fundamental point of view since they present interesting physical properties which have motivated numerous investigations in the past two decades (Eicher et al, 1986;Wenger et al, 1991;dos Santos & Oliveira, 1992;Kremer & Greedan, 1998;Mello et al, 1999;Antonietti et al, 2001;Eibschü t et al, 1967;Drew et al, 1993;Heid et al, 1996;Beurlen et al, 2008). Much fundamental research on the physical properties has also been performed on synthetic AB 2 O 6 compounds (Felten, 1967;Esmaeilzadeh & Grins, 2002).…”
Section: Introductionmentioning
confidence: 99%